Highly sensitive and selective electrochemical sensor for detecting imidacloprid pesticide using novel silver nanoparticles/mesoporous carbon/hematite ore ternary nanocomposite. Issue 5 (October 2022) - Rashed, Md.A.; Faisal, M.; Alsareii, S.A.; Alsaiari, Mabkhoot; Jalalah, Mohammed; Harraz, Farid A.
Abstract: The increasing use of neonicotinoid class of pesticides in agriculture is a major concern for environmental pollution and water resource and can cause adverse health effects. Herein, we report a novel electrochemical sensor for sensitive and selective determination of Imidacloprid (IMC) pesticide using Ag nanoparticles deposited on mesoporous carbon and naturally extracted hematite ore (Ag@Meso-C/Hematite Ore) nanocomposite. The morphology and surface structure of undoped hematite ore disclosed the combination of Fe2 O3 and Fe3 O4 phases with a nanorod shape, whereas the ternary nanocomposite showed homogenously dispersed carbon nanomaterials and AgNPs with an average diameter 6.65 nm over the naturally extracted ore. The electrocatalytic investigation demonstrated irreversible diffusion-controlled kinetics with four-electron and four-proton exchanged electro-reduction. Detection of IMC by linear sweep voltammetry (LSV) depicts a wide linear detection range (63 – 870 μ M) with a sensitivity 0.1955 μAμM -1 cm -2 and a detection limit 1.06 μM. Additionally, excellent sensitivity (0.8113 μAμM -1 cm -2 ) and a detection limit (0.257 μM) was ensured within a wide range of 10.80–195.50 µM using the amperometic technique. The excellent sensing performance is likely related to the combination of merits of the three different components of the ternary nanocomposite. Moreover, during the IMC detection, the Ag@Meso-C/Hematite Ore based sensor electrode exhibited a unique selectivity behavior and excellent reproducibility, repeatability, and storage stability. Finally, the current developed sensory system based on naturally occurring hematite ore can provide a good alternative as a sensitive approach for the detection of various target analytes in chemical sensing studies. Graphical Abstract: ga1 Highlights: Ag@Meso-C/Hematite Ore nanocomposite via facile sonication and photochemical reduction. Ag@Meso-C/Hematite Ore modified GCE as efficient imidacloprid sensor. High sensitivity 0.8113 µMµA -1 cm -2, low LOD 0.257 µM and wide range 10.80–195.50 µM. Good electrode repeatability, operational stability and recovery from real sample.